Targeting the right parameters in PAH remediation studies. (1st June 2021) - Davin, Marie; Colinet, Gilles; Fauconnier, Marie-Laure
Abstract: Contaminated land burdens the economy of many countries and must be dealt with. Researchers have published thousands of documents studying and developing soil and sediment remediation treatments. Amongst the targeted pollutants are the polycyclic aromatic hydrocarbons (PAHs), described as a class of persistent organic compounds, potentially harmful to ecosystems and living organisms. The present paper reviews and discusses three scientific trends that are leading current PAH-contaminated soil/sediment remediation studies and management. First, the choice of compounds that are being studied and targeted in the scientific literature is discussed, and we suggest that the classical 16 US-EPA PAH compounds might no longer be sufficient to meet current environmental challenges. Second, we discuss the choice of experimental material in remediation studies. Using bibliometric measures, we show the lack of PAH remediation trials based on co-contaminated or aged-contaminated material. Finally, the systematic use of the recently validated bioavailability measurement protocol (ISO/TS 16751) in remediation trials is discussed, and we suggest it should be implemented as a tool to improve remediation processes and management strategies. Graphical abstract: Image 1 Highlights: Research should expand the list of PACs studied in soil remediation. Aged- and co-contaminated material should receive more attention in remediation trials. Bioavailability measurement should be included in remediation trials. Abstract : This critical review discusses three scientific parameters that influence PAH-contaminated soil/sediment remediation studies and management: the choice of targeted compounds, the choice of experimental remediation material, and the use of bioavailability measurement in remediation trials.